Spectrum and Antibiotic Sensitivity Pattern of Bloodstream Bacterial Isolates from Septicemic Neonates - Mahmood, Tahir; Ali, Wahid; Quratulain; Waseem Butt, Rabia; Iqbal, Kulsoom; Kamran, Taiba (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate the etiology of neonatal sepsis. We aimed to explore the antimicrobial sensitivity patterns among neonates. Methodology: This observational-based study was conducted in POF hospital Wah Cantt from September 2020 to March 2021. We selected 300 sepsis patients based on the WHO neonatal sepsis screening tool. Blood samples were collected by trained laboratory technicians using the aseptic technique. Laboratory technicians prepared a 5cm (in diameter) patch of skin over the proposed site of venipuncture. We drew one ml sample of blood from a fresh venipuncture site. This blood was added to a bottle containing 5–10 mL of blood Agar culture media. Results: We observed that babies with less than 5 Apgar scores reported a high risk of neonatal sepsis. We observed gram-positive bacteria in 49 (55.7%) cases while 39 (44.3%) were reported gram-negative bacteria. At the time of diagnosis, we observed that 67.3% of cases of gram-positive bacteria were highly reported in the LONS group. Around 23 (63.3%) gram-negative bacterial isolates were from EONS. Regarding bacterial pathogen, we observed 22 (25%) cases of Coagulase-negative staphylococcus aureus and 18 (20%) were of E. coli which results in neonatal sepsis. Conclusion: Our results concluded that third-line antimicrobials can be a beneficial treatment for managing neonatal sepsis. However, failure of irst two antimicrobials was observed due to high utilization before an accurate diagnosis of neonatal sepsis.